2020
DOI: 10.4196/kjpp.2020.24.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of carvacrol on lipopolysaccharide-induced memory impairment in rats

Abstract: Neuroinflammation is an important process underlying a wide variety of neurodegenerative diseases. Carvacrol (CAR) is a phenolic monoterpene commonly used as a food additive due to its antibacterial properties, but it has also been shown to exhibit strong antioxidative, anti-inflammatory, and neuroprotective effects. Here, we sought to investigate the effects of CAR on inflammation in the hippocampus and prefrontal cortex, as well as the molecular mechanisms underlying these effects. In our study, lipopolysacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…31 Furthermore, carvacrol also attenuated behavioral deficits and memory impairment in a rat model possibly by enhancing brainderived neurotrophic factor (BDNF) associated with a decreased expression of TLR4 mRNA. 32 In another study, Melo et al demonstrated that carvacrol can mitigate depression-like symptoms by modulating dopamine levels. 33 Similarly, carvacrol attenuated ethanol-induced cognitive deficits by modulating MAPK cascade and mitochondrial pathways.…”
Section: Introductionmentioning
confidence: 99%
“…31 Furthermore, carvacrol also attenuated behavioral deficits and memory impairment in a rat model possibly by enhancing brainderived neurotrophic factor (BDNF) associated with a decreased expression of TLR4 mRNA. 32 In another study, Melo et al demonstrated that carvacrol can mitigate depression-like symptoms by modulating dopamine levels. 33 Similarly, carvacrol attenuated ethanol-induced cognitive deficits by modulating MAPK cascade and mitochondrial pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-three days after LPS injection, IL-6, IL-1β, TNF-α, cyclooxygenase-2 (COX-2), and NF-κB levels were measured in the hippocampus as based on a previous study [22]. ree rats from each group were severely anesthetized with 1.2% isoflurane and were sacrificed.…”
Section: Il-6 Il-1β Tnf-α Cox-2 and Nf-κb Measurementmentioning
confidence: 99%
“…Reaction. e expressions of inducible brain-derived neurotrophic factor (BDNF), TLR4, and nitric oxide synthase (iNOS) mRNA using RT-PCR were analyzed according to a previous study [22]. Total RNA was extracted from the hippocampus of each rat using TRIzol reagent.…”
Section: Total Rna Isolation and Reverse Transcription-polymerase Chainmentioning
confidence: 99%
“…3 Different mechanisms have been described concerning the effects of phenolic compounds on healthfor example, reducing expression of inflammatory factors, and increasing brain-derived neurotrophic factor (BDNF) expression, which has an important role in growth, survival, and preservation of neurons. 18 Other action mechanisms include modulation of the gut microbiota, 19 decreased cancer cell proliferation, and increased apoptosis induction. 20 In addition to the pharmacological interest in these compounds, their biological activities have also been explored in other industry sectors (Fig.…”
Section: Introductionmentioning
confidence: 99%